PÊNFIGO FOLIÁCEO IDIOPÁTICO FELINO - RELATO DE CASO - Santi, Julia Possebon; Lucio, Bruna Marquardt; Filho, Saulo Tadeu Lemos Pinto (Salão do Conhecimento, 2019)
Projeto de extensão realizado no curso de Medicina Veterinária da Universidade Federal de Santa Maria